2017
DOI: 10.18038/aubtda.300437
|View full text |Cite
|
Sign up to set email alerts
|

Ricinoleic Acid Methyl Ester (Rame): Synthesis, Characterization and Determination of Optimum Process Parameters

Abstract: Castor oil is a unique vegetable oil with peculiar features such as extremely high viscosity and unusual miscibility with short chain alcohol. This necessitates a comprehensive exploration of all process parameters in the transesterification of castor oil, which is rarely done for other vegetable oils. In this study, the methanolysis of castor oil using alkaline catalyst (potassium hydroxide, KOH) was investigated in a batch reactor via the conventional one-variable-at-a-time protocol. The effects of process p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
(62 reference statements)
1
0
0
Order By: Relevance
“…4 showed that the main fatty acid component was methyl linoleic and ricinoleate which accounted for about 50.1% of the character of the biodiesel. This was observed to align with the work of [ 16 , 17 , 41 , 112 ]. This ester is composed of an acid and a hydroxyl group that readily forms hydrogen and dipole-dipole bonds with methanol and glycerol.…”
Section: Resultssupporting
confidence: 89%
“…4 showed that the main fatty acid component was methyl linoleic and ricinoleate which accounted for about 50.1% of the character of the biodiesel. This was observed to align with the work of [ 16 , 17 , 41 , 112 ]. This ester is composed of an acid and a hydroxyl group that readily forms hydrogen and dipole-dipole bonds with methanol and glycerol.…”
Section: Resultssupporting
confidence: 89%